Modeling strength degradation in lead?rubber bearings under earthquake shaking. - Kalpakidis, Ioannis V.
Lead?rubber bearings are seismic isolators that have been used extensively to protect buildings, bridges and mission-critical infrastructure from the damaging effects of earthquake shaking. Under large-displacement cyclic motion, the strength of a lead?rubber bearing reduces due to energy dissipation and the resultant heating of the lead core. This paper proposes a method to incorporate strength degradation due to lead core heating in modeling the hysteretic behavior of lead?rubber bearings. The validity of the proposed model is investigated through comparing numerical and experimental results. The model is used to examine the effects of lead core heating on the dynamic response of an isolated structure.
Keywords: Lead?rubber bearing; Energy dissipation; Lead core heating; Hysteretic modeling; Bounding analysis; Seismic isolation